Plemljev trikotnik in negibne točke transformacij - Pucelj, Ivan (Obzornik za matematiko in fiziko, 2015)
"Construct a triangle if one side, its altitude and a difference of two angles along it are given" - this is an exercise in the geometry textbook that was used by professor Borštner who taught Josip Plemelj in the high school. This problem attracted professor Plemelj later in his life (especially during Christmas holidays), and so he found several different solutions.
Keywords: matematika; mathematics; naloge